SISTEM INFORMASI AKADEMIK SUB SISTEM :TRANSAKSI AKADEMIK DAN USE MANAGEMENT (STUDI KASUS : FAKULTAS TEKN UNIVERSITAS HALU OLEO) - La Ode Apriadi; Ika Purwanti Ningrum; Statiswaty Statiswaty (semanTIK, 2016)
The purpose of the research that has been conducted by the author is  to build and design an Academic Information System of Halu Oleo University that can maintain  academic data of Halu Oleo University. System  is built by the author focus on processing data related to academic transaction such Study Program Card and Post-Study Program Card, value weighting, standard of value, college student furlough application and transcript. In addition, this system also maintain data related to user management.   The author uses Unified Modeling Language (UML) as the system modeling language, PHP as programming language and MySQL as system database. The results of the testing that has been done on the system shows that the system can help users ( both students and lecturer) in the process of academic transaction such as bidding, creating Study Program Card and Post-Study Program Card, and also transcripts as well as perform user management more regularly. Keywords— Academic Information System, Academic Transaction, User Management.